Spectrophotometric Determination of Catecholamines Via Charge Transfer Complexation with Bromanil, Applications to Catecholamine Drug Formulations - HASAN, MAHMOOD A. (Science Journal of University of Zakho, 2013)
A simple, sensitive, rapid and low-cost spectrophotometric method for catecholamine (levodopa, methyldopa and dopamine) determination in pure and drug formulations is described. This method is based on the complexation reaction of catecholamine with bromanil. Absorbance of the resulting green colored products is measured at 741 nm for levodopa complex and, 738 nm for methyldopa and dopamine. Beer's Law is obeyed in a concentration range of 0.2 – 3.5 µg ml-1 for levodopa, 0.1 – 4.0 µg ml-1 for methyldopa, and 0.2 – 2.5 µg ml-1 for dopamine and the molar absorptivity is 38222, 41474, and 48202 l.mol-1 cm-1 for levodopa, methyldopa, and dopamine respectively, with an excellent correlation coefficient (r = 0.9974) for levodopa, and (r = 0.998) for both methyldopa and dopamine.. The results show a simple, accurate, fast and readily applied method to the determination of levodopa methyldopa, and dopamine in pharmaceutical products. The analytical results obtained for these products by the proposed method are in agreement with those of the official standard method.